2015
DOI: 10.3989/loquens.2015.018
|View full text |Cite
|
Sign up to set email alerts
|

Accent mark and visual word recognition in Spanish

Abstract: The present research aims at determining to what extent an orthographic error related to the accent mark affects the visual recognition of Spanish words. For this, we conducted two experiments of visual lexical decision (with no word production), in which Spanish-speaking participants were instructed to ignore the presence or the absence of the accent mark.Stimuli were composed of words originally without accent mark (OrNA for 'originally no accent'; Experiment 1) and words originally with an accent mark (OrWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Recent lexical decision experiments in Spanish have revealed that omitting the accent mark in a word does not entail longer word identification times (e.g., cárcel = carcel; Schwab, 2015; fácil-FÁCIL = facil-FÁCIL; Perea et al, 2020). These findings were interpreted in terms of accented and non-accented vowels activating the same abstract orthographic representations—note that accent marks in Spanish indicate lexical stress with no changes in vowel quality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent lexical decision experiments in Spanish have revealed that omitting the accent mark in a word does not entail longer word identification times (e.g., cárcel = carcel; Schwab, 2015; fácil-FÁCIL = facil-FÁCIL; Perea et al, 2020). These findings were interpreted in terms of accented and non-accented vowels activating the same abstract orthographic representations—note that accent marks in Spanish indicate lexical stress with no changes in vowel quality.…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical evidence using laboratory visual word recognition tasks has shown that omitting the accent mark in Spanish words with unambiguous spellings does not entail a processing cost for the readers. Using a lexical decision task (“does the letter string form a word?”) with skilled adult readers, Schwab (2015) found remarkably similar response times for words regardless of presenting the normative accent mark (e.g., cárcel) or not (e.g., carcel). (Of note, participants were asked not to pay attention to whether the accent mark was present/omitted.)…”
mentioning
confidence: 84%
See 3 more Smart Citations